Travel into the World of the letraheridos. Roberto Bolaño and the Salvation trough Writing - Bolognese, Chiara (Anales de Literatura Hispanoamericana, 2010)
This essay outlines what kind of literature Bolaño wanted to create and which was his literary project, through the study of his characters, considered as beaten letraheridos (1-5). It will describe the adventures and the projects of the real visceralistas of Los detectives salvajes (6-10), and then it will focus the essay on the “risk literature” born from the total fusion between the writer and his art. After all this, this pages will try to explain the difference between the real and the false poet (11-20). During their search for true literature, the characters try to reach the complete separation from their predecessors and masters, and they create a sort of “literature of the orphans” (21- 24). To succeed in all this, the characters begin a search for their masters which reaches its climax in the total dissolution not only of those who search but also of those who are searched (25-33). The literary work is the only thing that remains.